Jordanians’ Perspectives On Open Consent In Biomedical Research - Alrabadi N; Makhlouf H; Khabour OF; Alzoubi KH (Dove Medical Press, 2019)
Nasr Alrabadi,1 Hanin Makhlouf,2 Omar F Khabour,2 Karem H Alzoubi3 1Department of Pharmacology, Faculty Of Medicine, Jordan University of Science and Technology, Irbid, Jordan; 2Department of Medical Laboratory Sciences, Faculty of Medical Sciences, Jordan University of Science and Technology, Irbid, Jordan; 3Department of Clinical Pharmacy, Faculty of Pharmacy, Jordan University of Science and Technology, Irbid, JordanCorrespondence: Nasr AlrabadiDepartment Of Pharmacology, Faculty Of Medicine, Jordan University Of Science And Technology, Irbid 22110, JordanTel +962795994247Email nnalrabadi@just.edu.joIntroduction: The informed consent process is an integral step in biomedical research. However, the emergence of biobanks and the need for open consent (also called “broad” or “blanket” consent) create challenges to this process.Aims and methodology: A survey was used to examine Jordanians’ perspectives on open consent and reuse of stored samples in future research.Results: The majority of participants had positive perceptions of informed consent and its importance. In addition, they appreciated the challenges that are associated with multiple uses of their biospecimens. About 55% agreed to provide open consent for reuse of their donated biospecimens. Participants (75–80%) also agreed that issues such as the possibility of sharing samples with international research centers, storage duration, and use of biospecimens after their death should be clarified as part of open consent. The inconvenience of the re-contact process, trust in the research team, and the importance of biobanks were all associated with participants’ willingness to provide open consent (P<0.05). On the other hand, privacy and confidentiality, doubt about future use of samples, unknown storage period, and the possibility of cross-border sample sharing were significantly associated with participants’ reluctance to provide open consent.Conclusion: The majority of Jordanians accept the idea of open consent. Clarification of issues such as international sample sharing, duration of storage, domains of intended research, confidentiality, and privacy can provide more support for the use of open consent.Keywords: open consent, sample storage, sample reuse, biobank, human ethics, human research